Enhancement of curcumin's physicochemical properties by developing its eutectic mixtures - Ahlawat, Sunita; Budhwar, Vikas; Choudhary, Manjusha (Journal of Applied Pharmaceutical Research, 2024)
Background: Curcumin is a compound obtained from the rhizomes of Curcuma Longa. It has various pharmacological properties like anti-inflammatory, anti-oxidant, anti-hyperlipidemic, etc. However, it also has some limitations that restrict its use as a medicine. Material and method: In the present study, a eutectic mixture of curcumin and glycine (35% and 65%) was prepared to improve its dissolution rate and photostability, characterized by DSC, FTIR, and XRD studies. Result and discussion: After 40 minutes, the eutectic mixture dissolved 10-fold more than the parent drug. The photostability studies were conducted according to ICH Q1B guidelines; after the seventh day of accelerated photostability studies, curcumin-glycine eutectic mixtures showed 36% degradation, 34% less than pure curcumin. Conclusion: The present study revealed that the physicochemical properties of BCS class II drugs can be improved by forming an eutectic mixture.